2022
DOI: 10.1021/acs.macromol.1c02539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer on the Contact Line Friction of a Capillary Bridge

Abstract: When a small amount of polymer is added to a liquid capillary bridge between two solid surfaces under steady shear, the effective friction of the receding contact line increases. The critical factor of the determination of the contact line friction is the local polymer concentration near the contact line, which alters the liquid−solid interfacial tension. According to the modified equation of the molecular kinetic theory for polymer solutions, the capillary force has static and dynamic contributions from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The above picture becomes more involved when the spreading fluid is complex, such as a polymer solution (Lee & Müller-Plathe 2022), a polymeric melt (Seemann et al 2005) or a viscoplastic material (Spaid & Homsy 1996). Such fluids can have intrinsic time scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The above picture becomes more involved when the spreading fluid is complex, such as a polymer solution (Lee & Müller-Plathe 2022), a polymeric melt (Seemann et al 2005) or a viscoplastic material (Spaid & Homsy 1996). Such fluids can have intrinsic time scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Soleymaniha and Felts used atomic force microscopy (AFM) to study the spreading dynamics of molten polystyrene (PS) drops on various solid substrates, and dissipation mechanisms were also considered through the MKT and HD. Recently, Lee and Müller-Plathe performed an interesting numerical study of capillary bridges of polymer solutions and concluded that the wetting behavior is dependent on the local polymer concentrations near the contact line and the contact line friction is affected by the strongly surface-adsorbed polymer molecules. In these polymer systems, the chemical reaction is deliberately avoided.…”
Section: Introductionmentioning
confidence: 99%
“…This force was the unbalanced contact line force per unit length that arose from a contact angle different from Young’s equilibrium contact angle. Researchers have adapted this idea to model shearing bridges between flat plates using multibody dissipative particle dynamics simulations, surface energy minimization, lattice Boltzmann simulations, and experiments. , Similarly, it has successfully been used to model the tangential force arising from sliding drops. In both cases, the advancing and receding contact angles have been included in the tangential force equations. However, there is still a need to investigate the link between contact angle hysteresis and tangential forces for capillary bridges with changing heights.…”
Section: Introductionmentioning
confidence: 99%
“…In 1925, Adam and Jessop introduced a "line tension" that acted like friction to prevent contact line motion. 17 between flat plates using multibody dissipative particle dynamics simulations, 18 surface energy minimization, 19 lattice Boltzmann simulations, 20 and experiments. 19,21 Similarly, it has successfully been used to model the tangential force arising from sliding drops.…”
Section: Introductionmentioning
confidence: 99%